Dampak Likuiditas, Ukuran Perusahaan Terhadap Kinerja Keuangan di Perusahaan Otomotif - Nopriadi Nopriadi; Annisa Annisa (Student Scientific Creativity Journal, 2023)
This study aims to examine the effect of liquidity measured by the current ratio (CR), and firm size measured by the natural logarithm (Ln) of total assets against financial performance in companies in the otomotiver from 2017- 2021. The method of determining the sample used was purposive sampling. The sample used was 13 companies. The data analysis technique used is panel data regression analysis consisting of chow test, hausman test, using Eviews 9.0 software. Partially liquidity (CR) had did not a significant effect on financial performance (ROA). Whereas company size (Ln Total Assets) have negative a significant effect on financial performance (ROA).